ISM Policy Pervasion: Visas, Study Permits, and the International Student Experience - Crumley-Effinger, Max (Journal of International Students, 2023)
With more and more literature on international student mobility and migration (ISM), one area of focus has often been overlooked: the impacts of student visas and study permits. Examined through an institutionalist framework highlighting the influences of institutions on individuals and their agency, this study describes how visa and study permit policies pervade international students’ lives in a variety of ways. Interview data collected from 40 international students who study in Australia, Canada, and the United States were analyzed to uncover themes from these host countries. Drawing on these interviews to outline the concept of ISM policy pervasion, the findings of this study show that visa policies affect international students in wide ranging ways. In addition to providing empirical evidence for ISM policy pervasion, this article also lays the groundwork for further studies that delve into the practical impacts of student visa and study permit policies around the world.